Neonatal Hemochromatosis: Treatment with Exchange Transfusion and Intravenous Immunoglobulin - Ehab Mohamed Hantash; Abdulrahman Al Zahrani; Mohamed Abdoun; Syeda Naqvi; Georges E. Nawfal (Dr. Sulaiman Al Habib Medical Journal)
Neonatal Hemochromatosis (NH) is a rare phenotype of severe fetal/neonatal liver injury that is accompanied by extrahepatic siderosis. Current clinical evidence shows that NH is not a disease per se, but is the consequence of fetal liver injury. Gestational alloimmune liver disease is the cause of nearly all cases of NH. Affected babies may die in utero, or present postnatally with severe acute liver failure or decompensated congenital liver cirrhosis. Diagnosis depends on the demonstration of extrahepatic siderosis by Magnetic Resonance Imaging (MRI), buccal biopsy, or detection of complement C5b-9 complex on hepatocytes from liver biopsy. Prognosis is generally bad without treatment. Treatment with iron chelators and antioxidants is not helpful. The more recent treatment approach of exchange transfusion and Intravenous Immunoglobulin (IVIG) has shown favorable outcomes. In this report, we describe a case of NH that presented with liver cell failure and high serum ferritin. Diagnosis was confirmed by MRI by demonstration of siderosis in the liver and pancreas while sparing the spleen. The infant was successfully treated with a combination of exchange transfusion and IVIG, and discharged at age 30 days in good condition.